Roughness Suppression in Electrochemical Nanoimprinting of Si for Applications in Silicon Photonics. Issue 43 (27th September 2022) - Sharstniou, Aliaksandr; Niauzorau, Stanislau; Hardison, Anna L.; Puckett, Matthew; Krueger, Neil; Ryckman, Judson D.; Azeredo, Bruno
Abstract: Metal‐assisted electrochemical nanoimprinting (Mac‐Imprint) scales the fabrication of micro‐ and nanoscale 3D freeform geometries in silicon and holds the promise to enable novel chip‐scale optics operating at the near‐infrared spectrum. However, Mac‐Imprint of silicon concomitantly generates mesoscale roughness (e.g., protrusion size ≈45 nm) creating prohibitive levels of light scattering. This arises from the requirement to coat stamps with nanoporous gold catalyst that, while sustaining etchant diffusion, imprints its pores (e.g., average diameter ≈42 nm) onto silicon. In this work, roughness is reduced to sub‐10 nm levels, which is in par with plasma etching, by decreasing pore size of the catalyst via dealloying in far‐from equilibrium conditions. At this level, single‐digit nanometric details such as grain‐boundary grooves of the catalyst are imprinted and attributed to the resolution limit of Mac‐Imprint, which is argued to be twice the Debye length (i.e., 1.7 nm)—a finding that broadly applies to metal‐assisted chemical etching. Last, Mac‐Imprint is employed to produce single‐mode rib‐waveguides on pre‐patterned silicon‐on‐insulator wafers with root‐mean‐square line‐edge roughness less than 10 nm while providing depth uniformity (i.e., 42.9 ± 5.5 nm), and limited levels of silicon defect formation (e.g., Raman peak shift < 0.1 cm −1 ) and sidewall scattering. Abstract : Novel chip‐scale near‐infrared optics requires scalable fabrication of 3D freeform nano‐ and microstructures in silicon. This manuscript investigates the origin of silicon roughening during metal‐assisted electrochemical nanoimprinting and minimizes it to levels comparable with plasma etching. Functional imprinted rib waveguides on silicon‐on‐insulator wafers are demonstrated, paving the way for its broad use to micromachine 3D photonic devices at scale.